Heat-related illness in athletes - Howe, A. S.; Boden, B. P. (The American Journal of Sports Medicine, 2007)
Heat stroke in athletes is entirely preventable. Exertional heat illness is generally the result of increased heat production and impaired dissipation of heat. It should be treated aggressively to avoid life-threatening complications. The continuum of heat illness includes mild disease (heat edema, heat rash, heat cramps, heat syncope), heat exhaustion, and the most severe form, potentially life-threatening heat stroke. Heat exhaustion typically presents with dizziness, malaise, nausea, and vomiting, or excessive fatigue with accompanying mild temperature elevations. The condition can progress to heat stroke without treatment. Heat stroke is the most severe form of heat illness and is characterized by core temperature >104°F with mental status changes. Recognition of an athlete with heat illness in its early stages and initiation of treatment will prevent morbidity and mortality from heat stroke. Risk factors for heat illness include dehydration, obesity, concurrent febrile illness, alcohol consumption, extremes of age, sickle cell trait, and supplement use. Proper education of coaches and athletes, identification of high-risk athletes, concentration on preventative hydration, acclimatization techniques, and appropriate monitoring of athletes for heat-related events are important ways to prevent heat stroke. Treatment of heat illness focuses on rapid cooling. Heat illness is commonly seen by sideline medical staff, especially during the late spring and summer months when temperature and humidity are high. This review presents a comprehensive list of heat illnesses with a focus on sideline treatments and prevention of heat illness for the team medical staff.